Developing Islamic Religious Education Learning Videos in Fourth-grade Elementary School - Yuliani, Beti; Susilo, Mohamad Joko (The Indonesian Institute of Science and Technology Research, 2024)
It is known that several Islamic religion teachers in Yogyakarta, Indonesia have not made maximum use of videos in their learning. The purpose of this study was to develop learning videos for Islamic religious education in grade IV elementary schools, to test the quality of feasibility, and its application in learning, and to measure the effectiveness of using video media on student achievement. This study used a 4D model (Define, Design, Develop, and Disseminate), and the data were collected using questionnaires, tests, and documentation and analyzed using descriptive analysis. The results of the study showed that the product of learning video using the Wondershare Filmora application has met the eligibility quality in line with the small test results of media experts and material experts. The application of video media could run smoothly and enjoyably. The video was found to be capable of facilitating the learning process. The results of the student's assessment of the video for the readability test were very good. The video was found very effective in use in Islamic religious education learning and was capable of improving student achievement. Students' understanding was found to get better after learning with video, thus improving their learning achievement.